“Je serais très merciable”: Formulaic vs. Creatively Produced Speech in Learners’ Request-Closings - Warga, Muriel (Canadian Journal of Applied Linguistics, 2005)
This paper reports the findings of a study on intermediate classroom learners’ ability to perform appropriate formulaic sequences (FSs) for closing high-imposition requests. Based on a corpus of 1,200 requests it was found that FSs constitute a substantial part of French and Austrian native speakers’ request-closing behaviour. Classroom learners of French, on the other hand, are shown to use FSs significantly less frequently than native speakers. Moreover, the data provide convincing evidence that employing complex, situation-specific request-closings is a strategy learners draw upon to compensate for their lack of appropriate FSs. For instance, native speakers “offer a reward” by saying in very general terms Je te rendrai ça. Learners, by contrast, “offer a reward” in exactly the same situation by saying En contrepartie, je t’aiderai avec l’interrogation en maths. Furthermore, it was found that if learners do use formulaic language, the FSs they use are not necessarily the same as those used by native speakers. Therefore, the results of this study clearly suggest that the use of FSs differs considerably between native speakers and classroom learners not only at a quantitative but also at a qualitative level.